First successful outcomes of pegvaliase (PALYNZIQ) in children - Majid Alfadhel; Rayyan Albarakati (BMC, 2024)
Abstract Background PKU is an autosomal recessive hereditary inborn error of metabolism caused by a lack of phenylalanine hydroxylase enzyme activity. Pegvaliase (PALYNZIQ®) treatment has been approved to reduce blood Phe concentrations in adult phenylketonuria patients with uncontrolled blood Phe concentrations greater than 600 micromol/L on current management. However, data regarding individuals under the age of 16 is still unavailable. Case report We report a 12-year-old Saudi girl who underwent pegvaliase therapy and was closely monitored for one year. Remarkably, a positive therapeutic response became apparent six months after commencing pegvaliase treatment. Phenylalanine (Phe) levels showed significant improvement, stabilising within the < 5 to 14 µmol/L range on a regular diet without any restriction. At her current age of 12, the patient maintains an unrestricted dietary regimen, consuming a diverse selection of foods, including poultry, meat, and protein sources, all while consistently maintaining normal Phe levels with no change in mental status after treatment. The parents gave their written, informed consent in allowing the research study to be carried out and clinical data to be published. Conclusions This report addresses the potential broader applications of Pegvaliase in children, as well as its safety and tolerability in this age group. However, larger sample sizes and robust methodologies are required to validate such findings.